Land use pattern of selected sub-watersheds of the Siang river of Arunachal Pradesh using remote sensing and GIS techniques - DUTTA, H.; GOSWAMI, D. C.; KARMAKAR, R. M. (Journal of Soil and Water Conservation, 2021)
Geo-coded satellite images had been used for studying land use/land cover pattern of selected subwatersheds of Siang river covering parts of Arunachal Pradesh and Assam. Among different land use/ land cover classes in the study area, evergreen/semi-evergreen dense forest occupies the largest area (46.15 per cent) predominantly in hill slopes followed by settled cultivation in alluvial and flood plain areas (21.73 per cent). Other land use classes are scrub land (6.13 per cent), scrub forest (5.81 per cent), grass land / grazing land (2.46 per cent), shifting cultivation (1.62 per cent), forest plantation (0.34 per cent), river sand (8.01 per cent) and river/stream/nalah (6.51 per cent).